2016
DOI: 10.1098/rstb.2015.0084
|View full text |Cite
|
Sign up to set email alerts
|

Correlated pay-offs are key to cooperation

Abstract: One contribution of 18 to a theme issue 'The evolution of cooperation based on direct fitness benefits.' Subject Areas: behaviour, evolution, ecology Keywords: cooperation, reciprocity, commodity trading, direct fitness benefits, non-kin, decision rules The general belief that cooperation and altruism in social groups result primarily from kin selection has recently been challenged, not least because results from cooperatively breeding insects and vertebrates have shown that groups may be composed mainly of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
199
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 122 publications
(205 citation statements)
references
References 255 publications
(352 reference statements)
2
199
0
Order By: Relevance
“…According to current evidence, there are very few examples for punishment [15], while there are various examples for positive reciprocity [11]. Regarding partner switching, we are aware only of clear interspecific examples where partner switching in response to defection occurs.…”
Section: (D) Connection To the Empirical Literaturementioning
confidence: 92%
See 1 more Smart Citation
“…According to current evidence, there are very few examples for punishment [15], while there are various examples for positive reciprocity [11]. Regarding partner switching, we are aware only of clear interspecific examples where partner switching in response to defection occurs.…”
Section: (D) Connection To the Empirical Literaturementioning
confidence: 92%
“…An often-studied strategy using positive reciprocity as a partner control mechanism is tit-for-tat (TFT), which starts by cooperating and then in subsequent rounds implements the previous action of the partner [3 -5]. Although positive reciprocity is often favoured by selection in evolutionary models [3,[6][7][8], its relevance outside humans has been questioned ( [9], but see [10,11]). …”
Section: Introductionmentioning
confidence: 99%
“…Helping duties in cooperative breeders are highly variable between species, including vigilance behaviour and food provisioning in birds and mammals (Clutton‐Brock, ) and egg cleaning and fanning, shelter digging, and antipredator defence in fishes (Taborsky, ). Some of these behaviours, like food provisioning and care of foreign eggs or young, can be called altruistic, as they involve immediate fitness costs to the alloparent without immediate fitness benefits (as defined by Taborsky, Frommen, & Riehl, ). Other behaviours, such as antipredator defence and territory maintenance (e.g., shelter digging) might additionally have an immediately self‐serving component, especially when they are also shown in the absence of dependent young (Brouwer, Heg, & Taborsky, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the assistance that male olive baboons ( Papio anubis ) give each other to steal mates from rival males has been interpreted as direct reciprocity (Packer, ) and yet a simpler explanation might be that they gain immediate benefits from synchronizing their attacks (Clutton‐Brock, ). Many have concluded that there is a lack of evidence for reciprocity in non‐human species (Clements & Stephens, ; Dugatkin, ; Stevens & Hauser, ; Clutton‐Brock, ; West et al, ; although see Table 1 in Taborsky, Frommen & Riehl, ) and that mechanisms other than reciprocity are used to enforce cooperation in nature (West et al, ) including coercion (Clutton‐Brock & Parker, ; Clutton‐Brock, ) and partner choice and consent in ‘biological markets’ (NoĂŤ & Hammerstein, , ). Even in humans, although reciprocity is seen by some as a universal human characteristic (Broude, ; Krebs, ), others have failed to find evidence for it in exchanges within hunter–gatherer societies (Hawkes, ; Hawkes & Bliege Bird, ; although see Jaeggi & Gurven, ).…”
Section: Introductionmentioning
confidence: 99%